DOCTOR STRANGE - Derrickson, Scott; Feige, Kevin; Spaihts, Jon; Derrickson, Scott; Cargill, C. Robert; Cumberbatch, Benedict; Ejiofor, Chiwetel; McAdams, Rachel; Wong, Benedict; Stuhlbarg, Michael; Bratt, Benjamin; Adkins, Scott; et al. ([California] : Marvel Studios, 2017)
From Marvel Studios comes "Doctor Strange," the story of world-famous neurosurgeon Dr. Stephen Strange whose life changes forever after a horrific car accident robs him of the use of his hands. When traditional medicine fails him, he is forced to look for healing-and hope-in an unlikely place: a mysterious enclave known as Kamar-Taj. He quickly learns that this is not just a center for healing but also the front line of a battle against unseen dark forces bent on destroying our reality. Before long Strange-armed with newly acquired magical powers-is forced to choose whether to return to his life of fortune and status or leave it all behind to defend the world as the most powerful sorcerer in existence.
1080p high definition widescreen (2.39:1).
Casting by Sarah Halley Finn ; music supervisor Dave Jordan ; music by Michael Giacchino ; head of visual development Ryan Menerding ; visual effects supervisor Stephane Ceretti ; visual effects and animation by Industrial Light & Magic ; costume designer Alexandra Byrne ; edited by Wyatt Smith, Sabrina Plisco ; production designer Charles Wood ; director of photography Ben Davis ; co-producer David J. Grant ; executive producers Charles Newirth, Stan Lee, Victoria Alonso, Stephen Broussard, Louse D'Esposto.
Benedict Cumberbatch, Chiwetel Ejiofor, Rachel McAdams, Benedict Wong, Michael Stuhlbarg, Benjamin Bratt, Scott Adkins, Mads Mikkelsen, Tilda Swinton.
P13 (Parental Guidance 13).
Blu-ray disc.
In English, Chinese (Mandarin PRC), Portuguese (Brazil) and Thai ; with English ESL, Bahasa (Indonesia), Bahasa (Malaysia), Cantonese, Chinese (Mandarin Simplified), Chinese (Mandarin Traditional), Korean, Portuguese (Brazil) and Thai subtitles.
Keywords: Strange, Sylvia, -- (Fictitious character) -- Drama; Wizards -- Drama; Magic -- Drama